XBRL Technology Adoption and Consequences: A Synthesis of Theories and Suggestions of Future Research - Hela Borgi (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - This study is an appraisal of XBRL existing literature to find out what exists and what is lacking in the literature regarding the incentives of XBRL adoption, and its consequences. Motivation - The literature has not fully investigated the incentives of XBRL adoption and its consequences for the users of financial statements. The aim of this study is to synthesize current literature on XBRL adoption and its consequences. Idea - eXtensible Business Reporting Language (XBRL) is revolutionizing financial reporting on a global scale. It has the support of the world's most powerful institutions, including stock exchanges, central banks, standard setters, regulators, and other industry interests. It has attracted the attention of accounting researchers to better understand its influences on accounting and auditing professionals. Methodology - The current study uses qualitative research methods that includes a review and a synthesis of a variety of archival materials. Papers on XBRL are summarized under two main categories: incentives of XBRL adoption, and its consequences. Findings - The review suggests that the majority of publications are published in the second decade during 2011-2021 period. This result may imply that researchers try to give more answers for regulators, policy makers and standard-setters about issues related to the concrete implementation of XBRL in different contexts and countries. In addition, the current review notices that most of the previous studies that focus on the determinants of XBRL adoption are exploratory and use the qualitative method through surveys and/or interviews. While these studies extend our knowledge about the motivations that push towards the XBRL adoption, future studies could confirm these results with more objective measures. The current study notices that most prior studies focus on a single country, hence future research may use comparative analysis of XBRL adoption in different countries as it may offer a better understanding of the actual use of XBRL in diverse contexts. Further studies should consider emerging countries, and more particularly GCC countries, where XBRL technology adoption is mandatory and take into account the socio-economic culture of these countries. As a future direction, there is a need of investigation on the role of regulation in improving the use of XBRL and the extent of compliance with XBRL IFRS taxonomy. Future studies may also investigate the potential consequences of XBRL technology on financial reporting quality to give answers for standard-setters and policy makers. Contribution - Our research contributes to the existing literature by creating a foundational knowledge base that will be relevant to different stakeholders including, governments, practitioners, and researchers on the effects of implementing XBRL, as well as the relevance of such theories in explaining XBRL adoption.
Keywords: M41; O14; O33; 650; XBRL; Digital system; Accounting information; Regulation; Financial reporting; Positive accounting theory